(untitled) (Al-Academy, 2023)
The aim of this research is to find approaches between the communicative process and the teaching of art education. Postgraduate/Masters studies for the academic year 2022-2023.In the light of this tool, the researcher reached a number of results, most notably: The art education teacher performs his communicative role correctly, as well as his ability to use verbal and non-verbal expressions and positive reinforcement clearly for the benefit of his students, and stimulates the largest number of their senses